COMPARATIVE PHYTOTOXICITY OF SOME BENZOXAZINOIDS ON THE EARLY GROWTH OF SELECTED WEEDS - MUKTA CHUM,; DAIZY R. BATISH,; H. P. SINGH,; R. K. KOHLI, (The Bioscan, 2010)
Benzoxazinoids (or hydroxamic acids), the naturally occurring secondary plant metabolites, mainly in graminceous crops exhibit great structural diversity. The present study explored the phytotoxicity of five selected benzoxazinoids viz. 2-benzoxazolinone (BOA), 3-Methyl-2-benzoxazolinone (Me-BOA), 2-H-1, 4- benzoxazin-3(4H)-one (H-BOA), 6-Methoxy-2-benzoxazolinone (M-BOA) and 6-Hydroxy-2-benzoxazolinone (Hy-BOA) on the early growth (in terms of root shoot length) of three weeds namely Cassia occidentalis L., Echinochloa crus-galli (L.) Beauv. and Phalaris minor Retz. The results clearly indicate the negative influence of benzoxazinoids on weed growth. The effect in all cases was a function of concentration. In all test plants maximum effect was observed with the treatment of Me-BOA and M-BOA, followed by Hy-BOA, H-BOA and least incase of BOA. Seeds of E. crus-galli and P. minor were found to be more sensitive to benzoxazinoid treatment as compared to C. occidentalis